Sensitivity of the LHC isolated-γ + jet data to the parton distribution functions of the proton - Carminati, L; Costa, G; D'Enterria, D; Koletsou, I; Marchiori, G; Rojo, J; Stockton, M; Tartarelli, F (2013)
We study the impact of differential isolated-photon+jet cross sections measured in proton-proton collisions at a center-of-mass energy of √s= 7TeV on the parton distribution functions (PDF) of the proton. Next-to-leading-order perturbative QCD (pQCD) calculations complemented with the NNPDF2.1 parton densities, and a Bayesian PDF reweighting method are employed. We find that although the current data provide only mild constraints to the parton densities, future γ-jet measurements with reduced experimental uncertainties can improve our knowledge of the gluon density over a wide range of parton fractional momenta x as well as of the quarks at low x. © EPLA, 2013.